Frequency of Toxoplasma gondii in technologically advanced pig farms and sex as a risk factor - Carranza C., Fernando (2017)
The aim of the current study was to estimate the frequency of pigs from technologically advanced farms positive to toxoplasmosis and to evaluate the association between positive reaction and sex of the animal. Blood samples were collected in 240 animals in a slaughterhouse in Lima, Peru. Samples were analyzed by the indirect immunofluorescence assay (IFA). The frequency of pigs positive to toxoplasmosis was 21.7%. Sex as possible risk factor showed an Odds Ratio (OR) of 1.24 with confidence intervals of 0.88-3.06. It was concluded that there is an important frequency of positive pigs to toxoplasmosis and that sex has no influence in the presentation of this disease.